Explorations in Ottoman prehistory - Lindner, Rudi Paul (University of Michigan Press, 2007)
Providing an understanding of early Ottoman history, this book investigates who the Ottomans were, where they came from, where they settled and why, as well what sort of relationships they had with their neighbors, in the late thirteenth and early fourteenth centuries.